Lactose-free Dulce de leche: compositional characterization, browning and texture profile. Issue 4 (10th November 2021) - Pinto, Caroline Barroso dos Anjos; Renhe, Isis Rodrigues Toledo; Viana, Carolina Carvalho Ramos; Perrone, Ítalo Tuler; Oliveira, Luiz Fernando Cappa de; Stephani, Rodrigo
Abstract: Our objective was to elaborate lactose-free Dulce de leche (DL) and evaluate the influence of the hydrolysis of this sugar on the attributes of the products. Fluid milk used was divided into two portions and, in one of them, enzymatic hydrolysis of lactose was carried through. Next, the homogenization of milk was performed at 20 MPa. Four different treatments were studied. The final products were evaluated in relation to their composition and physico-chemical characteristics. The main results show that the homogenized lactose-free DL obtained a higher concentration of free 5-Hydroxymethylfurfural (HMF) (133.77 ± 3.42 μmol l −1 ). Consequently, browning was more intense due to Maillard Reaction. Texture parameters were higher (1611.00 ± 598.78 g hardness and 19.52 ± 2.46 g gumminess) when compared to the homogenized traditional product (28.45 ± 1.16 μmol l −1 free HMF, 437.17 ± 279.3 g hardness, and 406.20 ± 311.69 g gumminess). Lactose-free products are in high demand by consumers; however, the results of this work highlight the challenges to properly control the browning and the texture parameters of DL.